Simulasi Penerapan Teori Respon Butir dalam Perakitan Perangkat Tes Bahasa Arab di Prodi Pendidikan Bahasa Arab Fakultas Pendidikan Bahasa Universitas Muhammadiyah Yogyakarta - Wati, Ana Taqwa (Maharaat: Jurnal Pendidikan Bahasa Arab, 2019)
The application of item response theory in constructing Arabic Language test equipment took place at the Arabic Language Education Study Program, Faculty of Language Education, Universitas Muhammadiyah Yogyakarta. This theory will be applied in the selection of final exam questions for PBA students taking Al-Qawaid An-Nahwiyyah courses. The items used in this test were dichotomous, with 250 items, then filtered and only a few questions, looking at the level of ability of the students in the specified class. IRT was to define the nature or ability of the underlying scale in which growth would be measured. The item model used in this study was the dichotomous item model. The results of the simulation of the item response theory in the constructing Arabic Language test equipment from the question bank provided with 250 items, obtained four items that were following the expected target.